SOY PEPTONE AS A NON-ANIMAL ORIGIN NITROGEN SOURCE IN Salmonella typhi CULTURE MEDIUM FOR PRODUCTION OF Vi POLYSACCHARIDE AS A MATERIAL OF TYPHOID VACCINE - Rahmila, Triana
Typhoid fever is a multisystemic disease that can be prevented by using Vi polysaccharide-based vaccine. Vi polysaccharide is a virulence factor of Salmonella typhi, can be produced in high quantities when considering two important aspects of S. typhi strains and culture medium used at the time of cultivation. Currently PT. Bio Farma using S. typhi strain PT. Bio Farma production and Typhoid Growth Medium (TGM). One of the main components of the TGM medium is casamino acid, but the material is derived from animal casein, thus at risk of transmitting zoonostic disease. The purpose of this research is to know the performance of S. typhi strain PT. Bio Farma production and the effect of casamino acid replacement by soy peptone (modified plant-based TGM) as a nitrogen source to the Vi polysaccharide produced by S. typhi culture. The series of studies conducted are: S. typhi batch culture cultivation of strain PT. Bio Farma production and Ty2 in TGM medium; S. typhi batch culture cultivation in TGM and modified TGM medium; S. typhi batch culture cultivation in medium modified TGM with four different concentrations of soy peptone: 5 g/L, 10 g/L, 15 g/L and 20 g/L; and lastly, S. typhi fedbatch cultivation in medium modified TGM with 5 g/L soy peptone concentration, which at 4th hour fed with medium containing three different glucose concentrations: 1.5 g/L, 3 g/L and 6 g/L. The batch culture method was carried out in 1 L Erlenmeyer with 300 mL working volume, 200 ± 25 rpm agitation in 32 ± 0,1 º C, while for fedbatch method was used bioreactor 20 L, with final work scale ±11,9 L, 200–250 rpm impeller agitation, pH 6–8, DO 35%. The determinant variable is the biomass and Vi concentration. Biomass was obtained from measurement of dry weight and bacteria cell turbidity (OD600), whereas Vi concentration was measured using ELISA method. Statistical analysis t-test was used in the first and second studies, because both have five replications. Based on studies results obtained, S. typhi strain PT. Bio Farma production has the ability to produce Vi polysaccharide and a higher Vi production rate than the Ty2 strain, although the biomass produced by this production strain is lower than that of the Ty2 strain. Furthermore, the influence of casamino acid replacement by soy peptone produces S. typhi culture in soy peptone medium has higher biomass than casamino acid. However, it is necessary to develop the method of S. typhi cultivation in order to produce a higher Vi polysaccharide. From the third study it xi was found that the effect of soy peptone concentration of 5 g/L, 10 g/L, 15 g/L and 20 g/L in the four different culture mediums resulted in the maximum growth rate of S. typhi are 0,6 g biomass/L.jam. However, based on the yield of Vi and yield coefficient, soy peptone medium concentration of 5 g/L can be considered to be a potential medium. Recent research has shown that feeding medium containing glucose 1, 5 g/L can produce Vi polysaccharide three times higher that is 75.74 x 10-3 g/L, compared with feed medium contains glucose 3 g/L and 6 g/L. From this research concluded that S. typhi strain PT. Bio Farma production cultured using fedbatch method in medium modified TGM containing 5 g/L soy peptone and fed using feed medium containing glucose 1.5 g/L can be considered as a routine production method, because it is able to produce high Vi polysaccharide. However, a validation process is required to ensure that the polysaccharide Vi results are always stable.